2010
DOI: 10.1152/ajpregu.00325.2009
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin activates interleukin-6 transcription in mouse skeletal muscle in vivo and in C2C12myotubes in vitro

Abstract: Expression of the cytokine interleukin-6 (IL-6) by skeletal muscle is hugely increased in response to a single bout of endurance exercise, and this appears to be mediated by increases in intracellular calcium. We examined the effects of endurance exercise on IL-6 mRNA levels and promoter activity in skeletal muscle in vivo, and the role of the calcium-activated calcineurin signaling pathway on muscle IL-6 expression in vivo and in vitro. IL-6 mRNA levels in the mouse tibialis anterior (TA) were increased 2–10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 68 publications
(98 reference statements)
2
17
0
Order By: Relevance
“…Given that contraction-inducible CXC chemokines were up-regulated via JNK-, but not calcineurin-, mediated signaling cascades [18], expressions of each of these exercise factors appears to be differently regulated at the levels of signaling intermediates upon deciphering the complex contractile activity of muscle cells. In an excellent agreement with our observations, previous reports have indicated involvement of calcineurin activity in exercise-induced IL-6 expression in vivo as well as in ionomycin-induced IL-6 expression in vitro [23,28,29]. On the other hand, several lines of evidence have also indicated the involvement of JNK in exercise-induced up-regulation of IL-6 in working skeletal muscle [30] as well as in the EPS-evoked contracting myotubes [26].…”
Section: Intracellular Signals Involved In Eps-induced Il-6 Regulationsupporting
confidence: 92%
“…Given that contraction-inducible CXC chemokines were up-regulated via JNK-, but not calcineurin-, mediated signaling cascades [18], expressions of each of these exercise factors appears to be differently regulated at the levels of signaling intermediates upon deciphering the complex contractile activity of muscle cells. In an excellent agreement with our observations, previous reports have indicated involvement of calcineurin activity in exercise-induced IL-6 expression in vivo as well as in ionomycin-induced IL-6 expression in vitro [23,28,29]. On the other hand, several lines of evidence have also indicated the involvement of JNK in exercise-induced up-regulation of IL-6 in working skeletal muscle [30] as well as in the EPS-evoked contracting myotubes [26].…”
Section: Intracellular Signals Involved In Eps-induced Il-6 Regulationsupporting
confidence: 92%
“…However, this association was seen only in muscle low in glycogen, suggesting that this mechanism is not involved at the early onset of contraction-induced IL-6 transcription. Similarly, Allen et al (12) and others (11,31) have demonstrated in vitro and in vivo that the calcium-activated phosphatase calcineurin stimulates IL-6 expression during exercise/contraction. Calcineurin has many downstream transcription targets, including CREB (cAMP-responsive element-binding protein), MEF2, and NFAT, and initial speculation indicated that the latter may stimulate IL-6 mRNA (11).…”
Section: Discussionmentioning
confidence: 84%
“…2B). These data suggest that NFAT is in fact a repressor of IL-6 transcription and raise the question of whether calcineurin might increase IL-6 transcription via MEF2 (12) in exercising muscle in vivo (32).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been suggested that intracellular free Ca 2ϩ , acting as a second messenger, regulates the expression of IL-6 in skeletal muscle, possibly through the Ca 2ϩ -dependent phosphatase calcineurin (5,8,87). Also, another Ca 2ϩ -dependent process, possibly through the action of p38 MAPK and Ca 2ϩ /calmodulin-dependent kinase, has been reported to play a role on IL-6 expression related to intracellular glycogen content (17,87).…”
mentioning
confidence: 99%